Polystyrene nanoparticles: Sources, occurrence in the environment, distribution in tissues, accumulation and toxicity to various organisms - Kik, Kinga; Bukowska, Bożena; Sicińska, Paulina (Environmental pollution (1987), 2020)
Civilization development is associated with the use of plastic. When plastic was introduced to the market, it was assumed that it was less toxic than glass. Recently, it is known that plastics are serious ecological problem they, do not degrade and remain in the environment for hundreds of years. Plastic may be degraded into micro-particles < 5000 nm in diameter, and further into nanoparticles (NPs) < 100 nm in diameter. NPs have been detected in air, soil, water and sludge. One of the most commonly used plastics is polystyrene (PS) - a product of polymerization of styrene monomers. It is used for the production of styrofoam and other products like toys, CDs and cup covers. In vivo and in vitro studies have suggested that polystyrene nanoparticles (PS-NPs) may penetrate organisms through several routes i.e. skin, respiratory and digestive tracts. They can be deposited in living organisms and accumulate further along the food chain. NPs are surrounded by “protein corona” that allows them penetrating cellular membranes and interacting with cellular structures. Depending on the cell type, NPs may be transported through pinocytosis, phagocytosis, or be transported passively. Currently there are no studies that would indicate a carcinogenic potential of PS-NPs. On the other hand, the PS monomer (styrene) was classified by the International Agency for Research on Cancer (IARC) as a potentially carcinogenic substance (carcinogenicity class B2). Despite of the widespread use of plastics and the presence of plastic NPs of secondary or primary nature, there are no studies that would assess the effect of those substances on human organism. This study was aimed at the review of the literature data concerning the formation of PS-NPs in the environment, their accumulation along the food chain, and their potential adverse effects on organisms on living various organization levels. [Display omitted] •The studies suggest that polystyrene nanoparticles may penetrate organisms.•Polystyrene nanoparticles accumulate along the food chain.•Nanoparticles are surrounded by a protein corona that allows penetrating membranes.•In vitro and in vivo studies suggest that polystyrene nanoparticles could be toxic.•Currently there are no studies focused on their effect on human organism. PS-NPs are widely spread in the environment, penetrate living organisms and are toxic.